The Legislative Governance to Evaluate Job Performance - راضي, مازن ليلو; عبدالحميد, أحمد طلال (Journal of Legal Sciences, 2019)
Governance is a relatively modern term, specially in Arabic, it represents the Arabic translation of English word "Governance", This term refers to standards, approaches and policies to achieve quality and excellence in their application, the need to use these standards has emerged in the legislative field.Good legislation is characterized by efficiency, realism, transparency, fairness and predictability by those who address them.This research focuses on subjecting performance evaluation legislation to legislative governance standards to make this legislation high quality and effective.